Multi-omics analysis reveals the physiological and molecular response to cold stress in different spring wheat cultivars at the booting stage - Liu, Miao; Wu, Xiaoli; Li, Ming; Li, Shizhao; Xiong, Tao; Li, Chaosu; Tang, Yonglu (Frontiers in Plant Science, 2025)
IntroductionCold stress at the booting stage can seriously affect wheat growth, development and yield.MethodsTherefore, this study employed integrated physiological, transcriptomic, proteomic and metabolomic approaches to examine the response of two wheat cultivars, Chuanmai 104 (CM104, cold-tolerant) and Chuanmai 42 (CM42, cold-sensitive), to cold stress at the booting stage.ResultsThe viability of pollen in CM104 was less affected by low-temperature stress compared to CM42, ensuring a higher seed-setting rate in CM104. The young spike of CM104 also synthesized more osmoregulatory substances, endogenous hormones and higher antioxidant enzyme activities under the cold treatment compared to CM42. Transcriptome analysis identified 7,362 and 5,328 differentially expressed genes (DEGs) between control and cold-treated CM104 and CM42 spike samples, respectively. More DEGs, such as transcription factors, late embryogenesis abundant protein and hormone signalling transduction involved in the key regulatory pathways associated with cold tolerance were expressed in CM104. Proteomic and metabolomic analyses identified 173 differentially expressed proteins and 180 differentially accumulated metabolites between control and cold-treated CM104 spike samples, with some thought to enhance the cold acclimation of the variety. Integrative multi-omics analysis highlighted the critical roles of starch and sucrose, and glycerophospholipid metabolism in response to cold stress in CM104.DiscussionThis study uncovered the physiological changes, gene, protein and metabolite pathways involved in maintaining the osmotic balance and mitigating low-temperature stress in wheat spikes, and could serve as a crucial reference for selecting and breeding low-temperature tolerant wheat varieties.